The rare combination of low-grade thyroid-like nasopharyngeal papillary adenocarcinoma and squamous cell carcinoma: a case report and literature review - Toyran, Tugba; Inceman, Merve; Erdogan, Kıvılcım; Kücükosmanoglu, Aysegül; Ekici, Nur Yücel; Ugu, Aysun Hatice (Polish Journal of Pathology, 2022)
Thyroid-like low-grade nasopharyngeal papillary adenocarcinoma (TL-LGNPA) is an extremely rare neoplasm that generally originates from the nasopharynx surface epithelium. The case presented herein is of a 70-year-old male patient referred from another centre, who was observed to have this tumour together with squamous cell carcinoma. The clinicopathological findings of this combination are presented, which has very rarely been mentioned in the literature. Although the prognosis of TL-LGNPA is generally excellent, it may sometimes be combined with other tumours, and therefore it must be kept in mind that it could have a clinically more aggressive course.